Model wychowania w rodzinie ziemiańskiej w pierwszej połowie XIX wieku na przykładzie domu Stanisława Kostki Zamoyskiego i jego córki Celiny Działyńskiej - Wróbel-Lipowa, Krystyna (Biuletyn Historii Wychowania, 2013)
Upbringing of children in aristocratic families in the first half of the 19th century, based on Stanislaw Kostka Zamoyski and his daughter Celina Działyński Upbringing and education was a matter of great importance among the Polish landed gentry. The education of male descendants was particularly essential, because they were expected to hold important office, increase the family’s wealth and possessions and become a source of pride to the family in the future. According to Stanislaw Kostka Zamoyski XII, Majoratsherr in Zamość, the family home set the best example of upbringing to the younger family members. Therefore, children needed to have positive role models in their parents, who would provide them with advice, care and look after them. Small children were introduced to harsh conditions of everyday life. In order to positively shape children’s personalities, to help them to become open, gentle, reasonable, and kind people, teachers were not allowed to set them a bad example. The XII Majoratsherr’s children in Zamość were raised by parents who called for strict obedience and respect. Stanisław Kostka Zamoyski’s daughter Celina Działyńska raised her offspring in the same manner. She taught them respect for ordinary people – service and help for the needy. The above mentioned methods produced a positive effect in the future. Children raised in this way became aware of their responsibilities to the family and homeland.